Low-temperature behavior of disordered magnetic impurities: Distribution of effective Kondo temperatures - Zvyagin, A.A.; Makarova, A.V. (Физика низких температур, 2004)
Several rare-earth compounds, low-dimensional organic conductors, and spin chains exhibit
low-temperature divergences of their magnetic susceptibility and specific heat (non-Fermi-liquid
behavior). Such divergences are often related to disordered ensembles of magnetic impurities in
those systems. In this work the distribution function of the effective characteristic of a single magnetic
impurity, the Kondo temperature, is derived. We calculate how distributions of Kondo temperatures
depend on the effective dimensionality of the problem and on the concentration of impurities.